Newborn calf serum supplemented by tellurite as alternative transport medium for Corynebacterium diphtheriae. Issue 1 (November 2021) - Saraswati, R D; Nursofiah, S; Amalia, N; Hartoyo, Y; Puspandari, N; Sunarno,
Abstract: Indonesia is one of the five countries with highest diphtheria cases in the world. Laboratory confirmation by culture method as a gold standard requires bacterial survival. Indonesia's geographical condition as an archipelagic country and difficulties in transporting clinical samples are often obstacles in maintaining bacterial survival. This study aims to evaluate the ability of several transport mediums to maintain the survival of Corynebacterium diphtheriae . A total of 90 isolates were divided into nine groups of transport mediums. Samples were divided into 2 treatment groups, namely room temperature and temperature 2-8 ºC. On day 2, 4, 8, 16, and 32, 1 isolate from each group with 2 different incubation temperatures was cultured on blood agar medium and incubated for 24 hours at 37 ºC. Bacterial survival was indicated by the growth of suspect colonies which were identified by microscopic and biochemical tests. Results show serum with tellurite can be used with viability lower than silica gel, but higher than other media. Meanwhile at a temperature of 2-8 ºC, there are 2 types of the best transport medium, namely serum with tellurite and open silica gel in aluminum foil. Newborn Calf Serum supplemented with Tellurite can be used as an alternative transport medium for Corynebacterium diphtheriae, both at room temperature and at 2-8 ºC.